Towards a unified model of human development. Issue 2 (8th July 2019) - Haigh, Rex; Benefield, Nick
Abstract : Purpose: The purpose of this paper is to collaborate across disciplines to agree a better map of human development. Design/methodology/approach: This paper used an iterative process of consultation with professionals and specialists in relevant disciplines, and service users, continually refining the diagram and text until a "good enough" consensus was reached to produce a diagrammatic form and explanatory text. Findings: The process revealed a strong commitment across many disciplines to find a common contextual framework within which specialist understandings could be accommodated. The consultation process and iterative development of the diagram and text was marked by widespread interest and many detailed discussions. The substance of this paper is the result of that process. Research limitations/implications: The model places research in different specialist fields onto a single "map of the territory". It can encourage collaboration across disciplines when they are studying similar areas from different perspectives. It indicates the value of collaborative rather than competitive research enterprises. Practical implications: Too often, professionals involved in fields concerning human development become focussed within narrow frameworks of specialisation. The model supports better understanding of how different elements relating to developmental life interrelate. This can facilitate the basis upon which a wide range of training, education and research programmes can be formulated. Social implications: The model proposes greater use of a "whole-person/whole-life" perspective, which should allow greater integration between disparate approaches, and less experience of fragmentation. For a wide range of public sector activities, the quality of relational activity should be central to effective organisational and human outcomes. Without a unifying context, the understanding required to support relational work is weak: this model ad-dresses that deficit. Originality/value: This work is entirely original. It should be of value to all those interested in working in holistic ways; to policy makers wishing to avoid duplication, waste and ineffective interventions; and to researchers interested in working across disciplinary boundaries. Most importantly, it is for staff involved in health, justice, social care and education services at all levels. Their effectiveness relies on relational, as well as procedural working, and this model will support confidence in the primacy of these activities.